Developing creative-problem-solving-based student worksheets for transformation geometry course - Febriana Kristanti; Chusnal Ainy; Shoffan Shoffa; Siti Khabibah; Siti Maghfirotun Amin (Universitas Islam Negeri Maulana Malik Ibrahim, 2018)
Students’ reasoning ability in understanding the concepts in the Transformation Geometry course is still low. One of the causes is that there are no teaching materials, namely Student Worksheets that provide opportunities for students to be actively involved in creative learning processes; as a result, their reasoning skills are not well crafted. Therefore, it is necessary to develop a Student Worksheet that can strengthen students’ creative techniques and reasoning. The purpose of this study was to determine the feasibility of Student Worksheet products in terms of validity, practicality, and effectiveness. This research is an ADDIE development research whose stages comprise analysis, design, development, implementation, and evaluation. The instruments used in this study were validation sheets, student response questionnaires, learning outcomes, and learning implementation observation sheets. The results of this study were Creative Problem Solving (CPS) based Student Worksheet products in Geometry Transformation courses, and Student Worksheet eligibility, declared feasible in terms of (a) Validity; the worksheet validation results were in the very good category (4.36) (b) Practicality; the results of student response questionnaires to Student Worksheets were in a good category (31.16), and (c) effectiveness; the results of the test of student learning outcomes were in a good category (72%).